Urban development with lags - Bar-Ilan, Avner (1996)
"This paper specifies a model of urban development under uncertainty when there is a lag between the decision to begin a project and its completion. These lags have three important effects. First, the deterrent effect of uncertainty on development is smaller with lags than without them. Second, in some cases, development occurs later under uncertainty than with certainty. Third, lags may lead to leapfrog development, when distant land is developed prior to nearby land"
Keywords: Urbanization; Urban development